The functional connectivity profile of tics and obsessive-compulsive symptoms in Tourette Syndrome. (April 2020) - Bhikram, Tracy; Arnold, Paul; Crawley, Adrian; Abi-Jaoude, Elia; Sandor, Paul
Abstract: Tourette Syndrome (TS) is characterized by the presence of tics and sensory phenomena, such as premonitory urges, and is often accompanied by significant obsessive-compulsive symptoms (OCS). The goal of this exploratory study was to determine the association between functional connectivity and the different symptom domains of TS, as little is currently known about how they differ. Resting-state functional magnetic resonance imaging was performed in 39 patients with TS and 20 matched healthy controls. Seed-based functional connectivity of the supplementary motor area (SMA), orbitofrontal cortex (OFC), insula, caudate and putamen were compared between the groups, and correlated with clinical measures within the patient group. When compared to controls, patients with TS exhibited greater connectivity between the temporal gyri, insula and putamen, and between the OFC and cingulate cortex. Tic severity was associated with greater connectivity between the putamen and the sensorimotor cortex; OCS severity was associated with less connectivity between the SMA and thalamus and between the caudate and precuneus; and premonitory urge severity was associated with less connectivity between the OFC and sensorimotor cortex and between the inferior frontal gyrus and the putamen and insula seeds. Functional connectivity within sensorimotor processing regions were associated with all of the investigated symptom domains, including OCS, suggesting dysfunctions in the sensorimotor system may explain most of the observed symptoms in TS, and not just tics.